Dried blood spot characterization of sex‐based metabolic responses to acute running exercise. Issue 1 (5th February 2023) - Cendali, Francesca; D'Alessandro, Angelo; Nemkov, Travis
Abstract: Metabolomics and lipidomics techniques are capable of comprehensively measuring hundreds to thousands of small molecules in single analytical runs and have been used to characterize responses to exercise traditionally using venipuncture‐produced liquid samples. Advanced microsampling devices offer an alternative by circumventing the requirement to maintain frozen samples. This approach combines a microneedle puncture for blood draw with microfluidic sample collection onto a dried carrier and has thus far been employed for targeted measurements of a few analytes. To demonstrate the utility of advanced dried microsampling to characterize metabolomic and lipidomic changes during exercise, we obtained samples before and after a 2‐mile run from twelve (8 male, 4 female) healthy volunteers with various ranges in activity levels. Results highlighted significant changes in whole blood levels of several metabolites associated with energy (glycolysis and Tricarboxylic Acid cycle) and redox (Pentose Phosphate Pathway) metabolism. Lipid changes during this same period were individualized and less uniform. Sex‐based differences in response to running highlighted reliance on carbohydrate or fat substrate utilization in males or females, respectively. The results presented herein illustrate the ability of this approach to monitor circulating metabolome and lipidome profiles from field sampled blood in response to exercise.